Antipsychotics - a key line treatment for various psychotic symptoms - Kaur, Deepinder (International Journal of Basic & Clinical Pharmacology, 2024)
‘Psychosis’ is the state of mental disorder characterized by loss of contact with reality followed by delusions, hallucinations, disorganised thoughts etc. which mainly occurs because of the imbalance of neurotransmitters like dopamine, serotonin or glutamate. About 5-8% of people suffer from mental disorders in the whole world. In the earlier time it was difficult to treat such psychotic patients. So, when antipsychotics came in the market the treatment of such serious mental conditions became possible. Mainly two categories of antipsychotics are prescribed, out of which second generation are commonly prescribed because of their less adverse effects.